A Potential Approach between Ricoeur and Foucault: Hermeneutics and Technics of the Self - Delpech, María Beatriz (Revista de Humanidades de Valparaíso, 2018)
It is no coincidence that the relationship between Paul Ricoeur and Michel Foucault has been principally discussed in research carried out by specialists in one of these two thinkers. Although active at the same time, the scholar can easily get the impression that they worked in two parallel philosophical universes. This paper will argue, however, that a comparative reading is nonetheless possible. Taking identity and the subject as key areas of discussion, as well as the methodology used to deal with these themes, this paper will highlight the continuities between both the philosophers’ world views. A reading of their post-1980 works makes it clear that both of them, each in his respective way, can enrich a reading of the other and that, more than just being contemporaries, they share several important points in common.